2018
DOI: 10.1155/2018/8769563
|View full text |Cite
|
Sign up to set email alerts
|

Evolution Model of Health Food Safety Risk Based on Prospect Theory

Abstract: In the growing market of health food, certain disturbances occur, such as uneven quality of products, imitation of health food, prohibited drug content in health food, functional efficacy, and actual disagreement. The safety of health food has attracted wide attention from all walks of life. In this study, we constructed a three-party game model of health food safety risk evolution, which includes health food enterprises, health food consumers, and government regulators, based on prospect theory and evolutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…Evolutionary game analysis based on the behavior of participants has become one of the main tools of the analysis of food safety, this is because it can involve government, consumers, companies, and other subjects. Current studies from the perspective of the evolutionary game between the two participants mainly consist of games between the government and companies [ 28 ], and between food suppliers and manufacturers [ 29 ]; the studies from the perspective of tripartite participants mainly consist of games of governments, companies, as well as consumers [ 30 ].…”
Section: Methods and Modelsmentioning
confidence: 99%
“…Evolutionary game analysis based on the behavior of participants has become one of the main tools of the analysis of food safety, this is because it can involve government, consumers, companies, and other subjects. Current studies from the perspective of the evolutionary game between the two participants mainly consist of games between the government and companies [ 28 ], and between food suppliers and manufacturers [ 29 ]; the studies from the perspective of tripartite participants mainly consist of games of governments, companies, as well as consumers [ 30 ].…”
Section: Methods and Modelsmentioning
confidence: 99%
“…Luo et al developed a three-party game model of health food safety risk evolution, which includes health food enterprises, consumers, and government regulators. ey conclude that the influence mechanism of factors such as information search payment, consumers' subjective perception, and regulatory authority's certification affect food safety risks [28]. Based on the above, Luo et al argue that consumers' sensitivity to health food safety supervision information can help improve the profitability of enterprises [29].…”
Section: Food Safety Standards and Monitoring Evaluation In Localmentioning
confidence: 99%
“…rough simulation experiments, they found that false food safety information cannot be solved effectively, only relying on government supervision. Scholars construct food safety evolutionary game model from different theoretical perspectives [27][28][29]. e results showed that it is difficult to achieve the stable evolutionary strategy with the constraint conditions [27].…”
Section: Food Safety Standards and Monitoring Evaluation In Localmentioning
confidence: 99%
“…Of course, the tripartite evolutionary game theory also has a wide range of applications. For example, Jiang et al [26] constructed a threeparty game model that was analyzed and simulated by adopting dynamics to obtain the regulation strategies for an online shopping problem; Luo et al [27] constructed and researched a tripartite game model of health food safety risk evolution to provide a theoretical basis for effective market governance; Long et al [28] constructed a tripartite game model involving the government, consumers, and companies to explore the evolutionary equilibrium and the main driving factors for environmental problems; Liu et al [29] analyzed the stability of a coal mine safety monitoring system based on tripartite evolutionary game theory and proposed forward control schemes such as dynamic fines. erefore, it is reasonable and innovative to use the threeparty evolutionary game theory to study the cleaner production quality regulation strategy of the pharmaceutical.…”
Section: Related Literaturesmentioning
confidence: 99%